Hybridization and the Creation of “Third Spaces”: an Analysis of Two Works by Tomás Gubitsch - Munarriz, Alberto (Intersections, 2010)
Tango’s recent resurgence has greatly intensified the momentum of a long process of “international dissemination” that began with the genre’s arrival in Paris during the first decade of the twentieth century. The many dialogues promoted by this renewed popularity have set the stage for an unprecedented period of development marked by artistic collaboration, experimentation, and hybridization. As a result, the genre is undergoing numerous changes; among the most striking are the new sonic shapes it is assuming. Through the detailed analysis of two compositions by Argentine guitarist and composer Tomás Gubitsch, who since the 1970s—the time of the country’s notorious and brutal “Dirty War”—has resided in Paris, this paper examines some of the processes currently shaping the sonic form of some of tango’s numerous variants. This work hopes to shed light on Gubitsch the composer and on the current tango phenomenon itself, as well as to contribute to a better understanding of the ways musical hybrids are constructed.